Bedömning och sambedömning i förskola enligt förskollärares, chefers och rektorers skriftliga beskrivningar - Vallberg Roth, Ann-Christine (Utbildning & Lärande, 2021)
In Swedish preschools teachers seem to struggle with the concept of assessment in their day-to-day practices. The aim with this article is to build knowledge of how preschool teachers and managers/principals from eight Swedish municipalities characterise assessment and co-assessment in Swedish preschools. The material was generated in a 2018 survey completed by 240 respondents (85% response rate). A didaktik-oriented textual analysis was conducted. The results identify eight distinctive traces between the rejection and recognition of assessment in preschool. Assessment is preferably focused on learning in previous preschool studies. Co-assessment is repeatedly highlighted as an equality marker: "Co-assessment is for me that we are moving towards a more equal activity". Although assessment is preferably focused on learning, traces of teaching-oriented assessment also emerge. The concept of didaktik assessment is tested in relation to Learning-oriented assessment, LOA.